A Hybrid Plasminogen Activator Binds to the u-PA Receptor and Has a Reduced Thrombolytic Potency In Vivo - Asselbergs, Fred A M; Bürgi, Rolf; Hamerman, Jessica; Heim, Jutta; van Oostrum, Jan; Agnelli, Giancarlo (Thrombosis and Haemostasis, 1993)
Fibrinolytic properties of four hybrids of u-PA and t-PA, all containing the u-PA growth factor domain and binding to recombinant human u-PA receptor expressed in CHO cells, were compared. Highest fibrin stimulation was observed with uK2tPA which when compared to t-PA in the rabbit system, had a considerably prolonged circulatory half-life in vivo. Compared to an equimolar dose of t-PA, 0.4 mg/kg uK2tPA caused a similar consumption of α2-antiplasmin and fibrinogen and a considerably greater prolongation of the ex-vivo blood clotting time. Nevertheless, this dose of uK2tPA was inactive in the jugular vein thrombosis assay. This lack of thrombolytic activity is presumably due to the presence of a functional u-PA growth factor domain, which in binding uK2tPA to cellular blood elements possibly retards its penetration into the blood clot and in this manner could neutralize the potential thrombolytic activity of the t-PA kringle 2 and protease domains in uK2tPA.